Do the Math, please! - Raja Yusof, Raja Nerina; Hussin, Siti Rahayu; Hashim, Haslinda; Che Kadir, Che Nurul Khairunnisa; Mustafa, Muhamad Tajudin (Universiti Putra Malaysia, 2023)
This case focuses on HOME Math, an enrichment center dedicated to developing mathematical minds. It tells the story of Nurul, the company's founder, and her husband Tajudin, who aspired to expand their business. Their opportunity arose when investor Dato Anwar Sharil expressed keen interest in partnering with them. Nonetheless, HOME Math had to demonstrate to Dato Anwar that their HOME Math program was a viable and worthwhile venture for the future. This case study is particularly applicable for basic management, entrepreneurship, and strategic management courses.